Evaluation of the consolidation status of heavy oil sands through rock physics analysis: A case study from Fengcheng oilfield - Yuan, Hemin; Han, Xuehui; Zhang, Xin; Wang, Yang (Frontiers in Earth Science, 2023)
Heavy oil is an important unconventional oil resource with huge amount worldwide, which also forms the primary oil source in Fengcheng oilfield, XinJiang, China. Elastic properties and consolidation status of heavy oil sands are of significant values as they can provide guidance for reservoir exploration and production. However, due to the lack of detailed rock physics investigation of the heavy oil sands in Fengcheng oilfield, the knowledge about their micro-scale elastic properties and consolidation status is still limited. Based on the well log data and laboratory measurements, we performed rock physics analysis of the heavy oil sands’ elastic properties. We first analyzed the well logs to determine the oil sands formations and then quantitatively delineated the relations between density, porosity, and velocities. Combining with laboratory measured data, we applied theoretical rock physics models to characterize the consolidation status of the heavy oil sands. Our results show that the oil sands in this area are poorly consolidated with loose rock frame. Overall, this study highlights the micro-scale elastic properties of the heavy oil sands in Fengcheng oilfield and also reveals the consolidation status. It presents a method of integrating well log, laboratory data, and rock physics analysis to evaluate the consolidation status of heavy oil sands, which can facilitate the future detailed petrophysical analysis and provide important information for seismic characterization and drilling risk evaluation.